Design and Performance Analysis of a Floating Solar Power System in Situ Tunggilis - Fikri Adzikri; Evyta Wismiana; Waryani; Jaelani; Josua Panca Arjuna Manurung; Ahmad Zulfa Zulhilmi Rizqi (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2026)
Situ Tunggilis is a regional government asset managed by the Public Works Department of West Java Province and is part of an optimization plan by the Central Government through the Ministry of Public Works. One way to utilize the Situ Tunggilis area is by developing it as a tourist destination. To support this, adequate infrastructure such as public street lighting and reliable internet facilities is essential. The implementation of a Floating Solar Power Plant offers a sustainable solution to meet these energy needs, especially considering the limited available land and the demand for operational cost efficiency. This study focuses on designing a floating solar power plant system to supply independent energy for lighting and internet services in the tourist area. The approach involves technical calculations based on field measurements and secondary data, combined with system performance simulations. The simulation results demonstrate that the floating solar power plants system can meet the electricity demand for lighting and internet services in the pedestrian area, achieving a performance ratio of 71% and utilizing approximately 75% of the available solar energy. Moreover, the planned Wi-Fi network meets the required internet coverage radius for the tourist area.